A new selective culture medium for isolation of Burkholderia cepacia complex in pharmaceutical industry - Yu, Meng; Wang, Sijin; Zhong, Yao; Yuan, Li; An, Likang; Feng, Danyang; Liu, Zhen; Ma, Shihong (Frontiers in Microbiology, 2025)
ObjectivesBurkholderia cepacia complex (Bcc) are typical objectionable microorganisms of concern for water-based pharmaceuticals. In order to achieve quick and effective detection of Bcc to prevent final product contamination, a new selective medium, Burkholderia cepacia complex selective agar (BCCSA), for the detection of Bcc in water-based pharmaceutical products was reported.MethodsThe formulation of BCCSA was optimized based on the carbon sources utilization of 60 Bcc strains from multiple origins. BCCSA and Burkholderia cepacia selective agar (BCSA), which was adopted in the examination chapter for Bcc in United States Pharmacopoeia (USP), were compared in terms of growth-promoting, indicative and inhibitory properties using Bcc and non-Bcc strains. In addition to streaking and spreading on solid media, this study determined the growth curves of Bcc strains in liquid culture systems to discuss the growth-promoting ability of the two selective media from both qualitative and quantitative perspectives. 168 strains of non-Bcc were streaked onto the two media to compare inhibitory capability.Resultsα-D-Lactose was unable to be utilized by all 60 test Bcc strains, while Sucrose was used by some Bcc strains, hence the carbon source composition of the medium BCCSA was adjusted by replacing lactose with sodium pyruvate and reducing the amount of sucrose added. The initial pH value of the medium was set as 6.2 ± 0.2 at 25°C by adding potassium dihydrogen phosphate, taking into account the indication range of phenol red. The recovery of 16 Bcc standard strains on BCCSA showed no statistically significant difference compared to TSA (p = 0.68), whereas BCSA demonstrated a significant reduction (p = 0.03). When the experimental scope was extended to 40 strains mainly pharmaceutical related, BCCSA recovered a higher ratio (82% at 24 h incubation, 97% at 48 h) than BCSA (67% at 24 h, 90% at 48 h). It has been confirmed that the test Bcc strains exhibited higher growth rates in BCCSA by growth curve analysis (p = 0.02). For 168 non-Bcc strains, BCSA inhibited 94% of non-Bcc growth, while BCCSA inhibited 90%, with no significant difference.ConclusionThis novel medium BCCSA demonstrates enhanced efficiency and comparable selectivity in detecting Bcc in contrast to BCSA, rendering it more suitable for risk identification of Bcc in samples during pharmaceutical manufacturing process.